2005
DOI: 10.1056/nejmoa032782
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Risk Factors and Diabetic Neuropathy

Abstract: backgroundOther than glycemic control, there are no treatments for diabetic neuropathy. Thus, identifying potentially modifiable risk factors for neuropathy is crucial. We studied risk factors for the development of distal symmetric neuropathy in 1172 patients with type 1 diabetes mellitus from 31 centers participating in the European Diabetes (EURODIAB) Prospective Complications Study. methodsNeuropathy was assessed at baseline (1989 to 1991) and at follow-up (1997 to 1999), with a mean (±SD) follow-up of 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
555
12
17

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,124 publications
(656 citation statements)
references
References 35 publications
40
555
12
17
Order By: Relevance
“…Although the pathogenesis of DPN still has not been elucidated, several risk factors including hyperglycemia, dyslipidemia, smoking, etc. have been identified (2). Moreover, vascular diseases including cardiovascular disease, peripheral vascular disease, diabetic nephropathy, and diabetic retinopathy were all found to be risk factors of DPN (2,3).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the pathogenesis of DPN still has not been elucidated, several risk factors including hyperglycemia, dyslipidemia, smoking, etc. have been identified (2). Moreover, vascular diseases including cardiovascular disease, peripheral vascular disease, diabetic nephropathy, and diabetic retinopathy were all found to be risk factors of DPN (2,3).…”
Section: Introductionmentioning
confidence: 98%
“…have been identified (2). Moreover, vascular diseases including cardiovascular disease, peripheral vascular disease, diabetic nephropathy, and diabetic retinopathy were all found to be risk factors of DPN (2,3). A population-based study of type 2 diabetic patients in Sweden showed that the prevalence of peripheral sensory neuropathy increased with the severity of retinopathy and overt nephropathy, indicating that peripheral sensory neuropathy was associated with micro-or macro-angiopathy in type 2 diabetes (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies that have investigated the contributions of the individual components have revealed mixed results 15, 16, 17, 18, 19, 20, 21. We have recently shown that diabetes, prediabetes, and obesity are the main metabolic components associated with peripheral neuropathy in a United States obese population 22.…”
Section: Introductionmentioning
confidence: 99%
“…Additional risk factors for diabetic neuropathic pain have been proposed, including smoking, hypertension, obesity, hypercholesterolaemia and duration of diabetes (Tesfaye et al., 2005; Jensen et al., 2006). Epidemiological studies can identify risk factors and effective preventive strategies in parallel with the search for the underlying causative biological mechanisms, such as genetic pathways (Smith et al., 2007).…”
Section: Introductionmentioning
confidence: 99%